Mindfulness for Professional Caregivers of Coronavirus Disease-19- Positive Patients – A Realistic Need of the Hour - Sivasubramoney, Krishnan; Lekshmy, Kothandaraman (International Journal of Nursing Research, 2023)
Humankind has witnessed many natural and self-created traumatic events in its history. Among these, pandemics with major losses in terms of human force and other resources need special mention. The current situation of coronavirus disease (COVID-19) is one such. Most often health-care professionals (HCPs) who are the sole caregivers for patients with COVID-19 patients are at increased risk for infection and consequences more than general public. Extended working hours, changes in the mode of care, use of personal protection equipment, change of working and social environment, plummeting financial conditions, stressors within the family or in the personal life, and many such factors predispose HCPs to acute and ongoing stress. This is in addition to the routine stressors which any human being has exposure to. Often, this leads to adoption of inadequate and unscientific coping strategies with disastrous consequences in the long run. This article tries to elucidate on the utility and efficacy of mindfulnessbased interventions (MBIs) to enhance the resilience and psychological wellbeing of HCPs since subjective negative emotional states and inability to use life skills appropriately may accentuate the problems health care workers face in the taxing times of COVID-19 pandemic. MBIs have ample evidences to prove its effect in strengthening logical and emotional functions of brain to increase the resilience of practitioner. HCPs are the workforce of any country which need to adapt to changing situations and adopt the optimized methods and systems to meet the needs of patients, families, and society at large. Burnout is very common among these strata of professionals. Managing professional life and personal life in balance require added skills which mindfulness training can impart. Burnout, compassion fatigue, and post-traumatic stress disorder like problems which may get precipitated during the COVID-19 period may also be managed by MBIs.